CRIMINAL COMPLIANCE AS A MECHANISM FOR IMPROVING THE INVESTMENT CLIMATE: THE EXPERIENCE OF THE UNITED STATES AND UKRAINE - Viacheslav Tuliakov; Oleksandra Yanovska; James Holmes Armstead (Baltic Journal of Economic Studies)
The present article explores the function of criminal compliance as a legal and institutional mechanism for improving the investment climate, through a comparative analysis of criminal procedural frameworks in Ukraine and the United States. The study critically examines how differences in procedural statuses, particularly the presence of a formally defined "suspect" status in Ukraine and its absence in the U.S., affect legal certainty, fairness of proceedings, and overall investor confidence. Shaped by civil law traditions, the Ukrainian criminal process defines clear stages, such as "suspect", "charged" and "convicted", with distinct legal rights and obligations at each procedural point. By contrast, the US common law system does not recognise a formal "suspect" status. This divergence has critical implications for compliance practices. The US legal environment has developed a robust system of criminal compliance, based on early procedural safeguards such as Miranda rights, the exclusionary rule and due process protections under the Fourth, Fifth and Sixth Amendments. These safeguards reinforce accountability among law enforcement agencies and protect individuals' rights during pre-trial procedures. The administrative framework that underpins criminal processes is supported by strong and consistent legislative measures, with its foundations firmly rooted in the historical development of common law. This regime functions to provide predictability and consistency in the regulatory process, even before matters reach criminal jurisdiction. It also allows regulatory agencies to align their procedural enforcement activity with the areas of criminal jurisdiction that may arise earlier in the administrative enforcement process. Furthermore, tools such as the Foreign Corrupt Practices Act (FCPA), the U.S. Sentencing Guidelines, and OFAC regulations have led to the institutionalisation of corporate criminal liability and the incentivisation of internal compliance programmes as a means of avoiding legal exposure. These mechanisms contribute to transparent and predictable legal practices and play a key role in maintaining the country's attractiveness for foreign direct investment. In contrast, Ukraine's legal system, while increasingly aligned with European Union standards, still lacks a comprehensive and enforceable framework for criminal compliance, especially within law enforcement and public administration. Despite the legal establishment of procedural rights, their practical enforcement is hindered by legal uncertainty, inconsistent judicial practice, and occasional procedural overreach. These issues have the potential to compromise investor confidence, particularly among international firms that are apprehensive about exposure to corruption, arbitrary enforcement, and reputational risks. The article also evaluates the relevance of the EU Corporate Sustainability Due Diligence Directive (CSDDD), adopted in 2024, which imposes a legal duty on large companies to implement human rights and environmental due diligence across their operations and supply chains. Whilst the CSDDD is chiefly focused on the civil and commercial sectors, its implications for criminal law are extensive, particularly in terms of reinforcing risk-based internal governance and compliance standards. For Ukraine, aligning with CSDDD principles has the potential to act as a catalyst for more profound criminal justice reform, particularly by institutionalising preventive measures, fortifying procedural rights, and introducing internal compliance obligations within public and corporate structures. The article ultimately contends that the integration of CSDDD standards with the optimal practices of U.S. criminal compliance has the potential to substantially enhance Ukraine's legal infrastructure. The implementation of such reforms would engender legal certainty, reduce systemic risks, and foster a more predictable and transparent legal environment. Consequently, this would result in an improvement in the investment climate and provide support for the broader objectives of economic modernisation and European integration.